1996
DOI: 10.1084/jem.184.6.2109
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Fashigh CD4+ Synovial T Cells by Borrelia-reactive Fas-ligandhigh γδ T Cells in Lyme Arthritis

Abstract: The function of the minor subset of T lymphocytes bearing the γδ T cell antigen receptor is uncertain. Although some γδ T cells react to microbial products, responsiveness has only rarely been demonstrated toward a bacterial antigen from a naturally occurring human infection. Synovial fluid lymphocytes from patients with Lyme arthritis contain a large proportion of γδ cells that proliferate in response to the causative spirochete, Borrelia burgdorferi. Furthermore, synovial γδ T cell clones express elevated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 41 publications
4
90
1
Order By: Relevance
“…5) and the timely resolution of cellular lesions (Table II) were dependent upon the expression of a functional FasL by ␥␦ T cells. Our data demonstrating a role for the Fas/FasL pathway in recovery from autoimmunity are consistent with the role of ␥␦ T cell FasL-induced apoptosis of target cells expressing Fas in Borrelia-induced Lyme arthritis in humans (35) and in a mouse model of myocarditis caused by viral infection (6).…”
Section: Discussionsupporting
confidence: 72%
“…5) and the timely resolution of cellular lesions (Table II) were dependent upon the expression of a functional FasL by ␥␦ T cells. Our data demonstrating a role for the Fas/FasL pathway in recovery from autoimmunity are consistent with the role of ␥␦ T cell FasL-induced apoptosis of target cells expressing Fas in Borrelia-induced Lyme arthritis in humans (35) and in a mouse model of myocarditis caused by viral infection (6).…”
Section: Discussionsupporting
confidence: 72%
“…Evidence supporting selective ␥␦ ϩ cell lysis of CD4 ϩ lymphocytes comes from studies in Lyme arthritis (26) and from CVB3-induced myocarditis (12). In the latter studies, ␥␦ ϩ cells directly killed differentiated Th2 cell lines through Fas-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that only specific ␥␦ ϩ cell populations may participate in disease processes. How ␥␦ ϩ cells participate in disease is also complex, as both beneficial and detrimental roles have been attributed to these cells in various experimental models (23)(24)(25)(26). Previously, we have demonstrated that different subpopulations of ␥␦ ϩ T cells, based on their V␥/V␦ use, were activated in the resistant (C57BL/6) vs the susceptible (Bl.Tg.E␣) mouse strain following infection with CVB3, with V␥1 cells dominating in the former and V␥4 cells dominating in the latter strain.…”
mentioning
confidence: 99%
“…ϩ T cells, as demonstrated using human synovial T cells activated by Borrelia burgdorferi (92) and in a mouse model of coxsackievirus-induced myocarditis (31). In both these studies CD4…”
Section: Figure 6 Tcr␥␦mentioning
confidence: 99%